Rediscovering John Donne's Catalogus librorum satyricus. (5th February 2018) - Smith, Daniel Starza; Payne, Matthew; Marshall, Melanie
ABSTRACT: This article introduces a previously unknown manuscript copy of a satirical book-list in Latin by John Donne, known as the Catalogus librorum satyricus or The Courtier's Library . The manuscript (which we call WA2) was discovered at Westminster Abbey in autumn 2016, and is the earliest surviving witness of the Catalogus . A transcription of the new copy is supplied, with textual and bibliographical observations, an examination of its provenance, and the history of the work's publication in print and manuscript; we also speculate on WA2's arrival into the Abbey. The article argues for an original composition date of late summer 1603 to late autumn 1604, the most precise yet proposed for this work. It includes a new translation of Donne's only surviving Latin letter, to Sir Henry Goodere, which refers directly to the Catalogus . This letter is used to explicate the place of the Catalogus in Donne's life and writing, and to clarify issues of dating and circulation. The discovery of WA2 also provokes the reappraisal of another Catalogus manuscript at Trinity College, Cambridge (CT2). Previous scholars have identified this as an authorial revision and linked it to Donne's association with the Drury family in 1610–1611. The textual and circumstantial evidence of WA2 is marshalled to reject not only this later date and the Drury association, but the notion that Donne himself made the revision recorded in CT2.